2009
DOI: 10.3201/eid1501.081080
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Candidatus Bartonella melophagi from Human Blood1

Abstract: Candidatus Bartonella melophagi was isolated by blood culture from 2 women, 1 of whom was co-infected with B. henselae. Partial 16S rRNA, RNA polymerase B, and citrate synthase genes and 16S-23S internal transcribed spacer sequences indicated that human isolates were similar to Candidatus B. melophagi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 15 publications
1
72
0
1
Order By: Relevance
“…Bartonella spp. enfeksiyonları arasında kedi tırmığı hastalığı, basiller anjiomatozis, basiller peliozis, Carrion hastalığı, enfektif endokardit ve özellikle insan immünyetmezlik virüsü (HIV) pozitif olgularda nörolojik sendromlar sayılabilir 3,5 . Ülkemizde Bartonella'lara bağlı kedi tırmığı hastalığı ve basiller anjiomatozis olgu sunuları bulunmaktadır [6][7][8][9] .…”
Section: Introductionunclassified
“…Bartonella spp. enfeksiyonları arasında kedi tırmığı hastalığı, basiller anjiomatozis, basiller peliozis, Carrion hastalığı, enfektif endokardit ve özellikle insan immünyetmezlik virüsü (HIV) pozitif olgularda nörolojik sendromlar sayılabilir 3,5 . Ülkemizde Bartonella'lara bağlı kedi tırmığı hastalığı ve basiller anjiomatozis olgu sunuları bulunmaktadır [6][7][8][9] .…”
Section: Introductionunclassified
“…While Dehio and coauthors (9) suggested that B. schoenbuchensis transmitted with the bites of deer ked may establish a local infection in the skin and thereby contribute to the etiology of deer ked dermatitis, there is limited evidence to support a role for the ruminant-infecting Bartonella, such as B. schoenbuchensis, B. capreoli, B. melophagi, or B. chomelii, as zoonotic agents. Recently, Maggi and coauthors (42) reported isolation of the closely related "Candidatus Bartonella melophagi" from the blood of two diseased women, but no causal relationship between the disease and the infection was proven.…”
Section: Figmentioning
confidence: 99%
“…B. melophagi has been isolated from various lots of commercial defibrinated sheep blood in the United States (20). Interestingly, this species has also been isolated from the blood of two female patients, and it has been described as a new human pathogen (21). Although a high prevalence of this pathogen has been found in the sheep ked Melophagus ovinus (22,23), which is the potential vector of this Bartonella species, others studies have failed to identify Bartonella infection in sheep (16,22).…”
mentioning
confidence: 99%